Predictors of clinical success after transcatheter para-valvular leak closure: an international prospective multicentre registry. (3rd October 2022) - Hascoet, S; Smolka, G; Brochet, E; Bouisset, F; Leurent, G; Thambo, J B; Combes, N; Bauer, F; Nejjari, M; Pilliere, R; Dauphin, C; Bonnet, G; et al.
Abstract: Background: Prosthetic paravalvular leaks (PVLs) are associated with congestive heart failure and haemolysis, for which the standard treatment is open-heart surgery with the attendant risks to the patient. Transcatheter closure has emerged as an alternative. Patient selection criteria for the best option are needed. We aimed to identify predictors of clinical success after transcatheter PVL closure. Purpose: We aimed to identify predictors of clinical success after transcatheter PVL closure. Methods: Consecutive patients referred to 24 European centres for transcatheter PVL closure in 2017–2019 were included in a prospective registry (Fermeture de Fuite ParaProthétique, FFPP). Clinical success was absence of any of the following within 1 month: re-admission for heart failure, blood transfusion, open-heart valvular surgery, and death. Results: We included 216 symptomatic patients, who underwent 238 percutaneous PVL closure procedures on the mitral (64.3%), aortic (34.0%), or tricuspid (1.7%) valve. The prosthesis was mechanical in 53.3% and biological in 45.3% of procedures. All patients were symptomatic with heart failure, haemolytic anaemia, and the association of both conditions in 48.9%, 7.8% and 43.3%. One, two and three PVL were addressed during the same procedure in 69.6%, 26.6% and 3.8% respectively. Mitral and aortic PVL were severe in 35.3% and 13.8% (p<0.001). PVL was punctiform or extended to 1/8 or 1/4 of valve circumference in 18.6%, 52.4% and 28.1% of cases. A total of 331 devices were implanted. More than one device (up to 5) was implanted in 34.2% of procedures. Vascular plug 3, muscular ventricular septal defect occluder, vascular plug 2 and paravalvular leak device were the most frequently used devices, implanted in 45.0%, 16.0%, 14.2% and 13.6%, respectively. Successful device(s) implantation(s) within the leak and leak reduction ≤ grade 2 occurred in 85.0% and 91.4% of patients with mitral and aortic procedures, respectively (p=0.164), with major intra-procedural adverse event rates of 3.3% and 1.2%, respectively (p=0.371). The clinical success rates were 77.8% and 88.9% following mitral and aortic procedures, respectively (p=0.01). By multivariate logistic regression analysis, technical failure, mechanical valve and haemolytic anaemia were independently associated with absence of clinical success (odds ratios [95% CIs]: 7.7 [2.0–25.0], p=0.002; 3.6 [1.1–11.1], p=0.036 and 3.7 [1.2–11.9], p=0.025; respectively). Conclusion: Transcatheter PVL closure is efficient and safe in symptomatic patients but is more challenging and associated with an increased risk of clinical failure when performed in patients with hemolysis and/or on a mechanical valve. Funding Acknowledgement: Type of funding sources: Private hospital(s). Main funding source(s): The study is promoted and financially supported by Groupe Hospitalier Paris Saint Joseph